Diversities and interactions of phages and bacteria in deep-sea sediments as revealed by metagenomics - Sun, Xumei; Jiang, Haibo; Zhang, Siyuan (Frontiers in Microbiology, 2024)
Phages are found virtually everywhere, even in extreme environment, and are extremely diverse both in their virion structures and in their genomic content. They are thought to shape the taxonomic and functional composition of microbial communities as well as their stability. Amount of works in laboratory culture and viral metagenomic studies providing deeper insights into the abundance, diversity, distribution and the interaction with hosts of phages across a wide range of ecosystems. However, most of them were focused on easily accessible samples, such as soil, lake and shallow ocean, little is known about bathypelagic phages. Here, through analyzing the 16S rRNA sequencing and viral metagenomic sequencing data of 25 samples that collected from five different bathypelagic ecosystems, we detected the high diversity of bacteria and phages, particularly in the cold seep and hydrothermal vent, which have stable chemical energy. The relative abundance of phages in there were higher than in other three abyssal ecosystems. The low phage/host ratios that obtained from host prediction were differ from shallow and indicated the prevalence of prophages, suggesting the complexity of phage-bacteria interactions in abyssal ecosystems. In the correlation analysis, we revealed several phages-bacteria interaction networks of potential ecological relevance. Our work contributes to a better understanding of the interactions of bathypelagic bacteria and their phages.